Epidemiology of Coronavirus Disease 2019 in Yamagata Prefecture, Japan, January–May 2020: the Importance of Retrospective Contact Tracing - Seto, Junji; Aoki, Yoko; Komabayashi, Kenichi; Ikeda, Yoko; Sampei, Mika; Ogawa, Naomi; Uchiumi, Yumiko; Fujii, Shunji; Chiba, Masami; Suzuki, Emiko; Takahashi, Tatsuya; Yamada, Keiko; et al. (Japanese Journal of Infectious Diseases, 2021)
Public health interventions have played an important role in controlling coronavirus disease 2019 (COVID-19), which is a rapidly spreading infectious disease. To contribute to future COVID-19 countermeasures, we aimed to verify the results of the countermeasures employed by public health centers (PHCs) against the first wave of COVID-19 in Yamagata Prefecture, Japan (Yamagata). Between January and May 2020, 1,253 patients suspected of SARS-CoV-2 infection were invited for testing. Simultaneously, based on retrospective contact tracings, PHCs investigated the infection sources and transmission routes of laboratory-confirmed COVID-19 cases and tested 928 contacts. Consequently, 69 cases were confirmed between March 31 and May 4, 58 of whom were from among the contacts (84.1%; 95% confidence interval [CI] 75.5–92.7). The spread of infection was triggered in cases harboring epidemiological links outside Yamagata. Subsequently, the number of cases rapidly increased. However, PHCs identified epidemiological links in 61 (88.4%; 95% CI 80.8–96.0) of the 69 cases, and transmission chains up to the fifth generation. Finally, the spread of infection ended after approximately one month. Our results indicate that the identification of infection sources and active case finding from contacts based on retrospective contact tracing was likely to be an effective strategy in ending the first wave of COVID-19 in Yamagata.